Risk assessment in non-standard forms of civil engineering consulting services - Piyadasa, WM Sarath C; Hadikusumo, Bonaventura H. W. (Journal of Civil Engineering and Management, 2014)
Although a large body of research exists on risk assessment in civil engineering projects and of owners, contractors, concessionaires and financiers of such projects, there is a lacuna in such research on engineering consultants, particularly those associated with non-standard forms of consulting services. This paper seeks to explore the genesis of the underlying risks in non-standard forms of engineering consulting services, systematically classify the risks, and develop a Risk Breakdown Structure and a generic Framework for efficient assessment of these risks, which is a prerequisite for sound risk management in the engineering consulting industry. The research adopts a mixed method approach, synthesising exploratory type multiple-case studies and questionnaire surveys, carried out in 14 engineering consulting firms having extensive experience in the delivery of non-standard consulting services. This paper provides empirical insights of the genetic makeup of risks associated with non-standard forms of consulting services. Such risks are found to be predominantly linked to design office based activities that underline the importance of design function in engineering consulting practice. Loss of reputation and/or goodwill is rated as the most severe potential impact on consultants. Proposed Risk Assessment Framework provides the engineering consulting industry with a functional tool for efficient risk management.